NEOTECTONIC RANK MAPS OF SOUTH-WEST HISSAR - Umurzakov, Rakhimjan; Dononov, Jasur (Innovatsion texnologiyalar, 2024)
The article describes the neotectonic maps of Southwest Gissar based on rank analysis methods. It is noted that all previous tectonic maps represent an interference pattern of overlapping elements formed as a result of various factors and their use leads to erroneous results. The methods developed on the basis of the new rank analysis methodology were used for the first time in the creation of neotectonic maps in South-Western Hisar region. Features of neotectonic maps of three ranks were obtained and described for Southwestern Gissar. Taking into account previous information on South-West Hisar, a generalized neotectonic map was created with the help of modern technologies, and it was divided into three ranks based on the rank approach.